Polymeric membrane synthesis, modification, and applications : electro-spun and phase inverted membranes - Das, Chandan; Gebru, Kibrom Alebel (CRC Press, Taylor & Francis Group, 2019)
"The book illustrates fundamental concepts of preparation, characterization and modification of electro-spun and phase inverted polymeric membranes and presents their recent advancements for specific applications to the readers"--Resumé vydavatele
Keywords: polymerní membrány; polymery; elektrostatické zvlákňování; polymer membranes; polymers; electrospinning; monografie; monographs